FENOMENA KEDWIBAHASAAN DI SEKOLAH DASAR; SEBUAH KONDISI DAN BENTUK KESANTUNAN BERBAHASA - Syaiful Bahri (Universitas Kanjuruhan Malang, 2018)
Building language ethics, there is a pattern of attitude that must be conveyed as a moral message, ranging from manners and and asor that is good character and good manners in communication ethics, all derived from someone's politeness. This study examines the politeness of language and the phenomenon of bilingualism between students and teachers, principals, TU staff, gardeners and with fellow students. During this time, bilingualism can be found in adolescents, adults and even elementary school age children who have mastered the first language (B1) of regional languages ​​(Madura), and second language (B2) is Indonesian or vice versa. This research is a field research with a qualitative form, meaning that it examines the politeness of language with the phenomenon of bilingualism. Research focuses on analyzing words (written) or behaviors of individuals or groups. In fourth grade students of SDN Nyapar and SDN Batubelah there is a context of sub-ordinative (complex) bilingualism. Sub-ordinative language is bilingualism which shows that when using B1 (mother tongue) an individual often includes elements of B2 (Indonesian).